2017
DOI: 10.1055/s-0041-1728968
|View full text |Cite
|
Sign up to set email alerts
|

Uterine Artery Embolization for Management of Placenta Accreta, a Single-center Experience and Literature Review

Abstract: Abstract“Morbidly adherent placenta” is a term that describes the continuum of placenta accreta, increta, and percreta. Placenta accreta is the least invasive form, whereas placenta percreta represents a complete penetration of the trophoblast through the uterus that reaches the serosal surface and potentially invades the bladder, rectal wall, and pelvic vessels. Leaving the placenta in situ in the setting of abnormally invasive placenta is now widely practiced. We herein present three cases of abnormal placen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
0
0
Order By: Relevance
“…They concluded that the conservative approach reduced peripartum hysterectomy, injury to adjacent organs, and massive blood transfusions while conserving fertility. However, they followed a conservative management style where the placenta was left in situ, followed by methotrexate [10].…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that the conservative approach reduced peripartum hysterectomy, injury to adjacent organs, and massive blood transfusions while conserving fertility. However, they followed a conservative management style where the placenta was left in situ, followed by methotrexate [10].…”
Section: Discussionmentioning
confidence: 99%